Morgan Life Sciences - Flaumenhaft, Ben, (SAGE knowledge. Cases., 2016)
Morgan Life Sciences was a biotechnology firm headquartered in Waltham, Massachusetts. Initially, it focused on generic and over-the-counter medications, which it manufactured and distributed to drugstores and supermarket chains. Morgan completed a successful initial public offering in 1994, but by the late 1990s, the generics market had become increasingly competitive. Morgan steadily lost ground as its larger, low-cost competitors pushed prices relentlessly downward. This study explains how CEO Wendy Shaw set about transforming the fortunes of the company.